Decision-making for dummies - Jones, Dawna (John Wiley & Sons, 2014)
Today's business leaders have to face the facts—you can't separate leadership from decision making. The importance of making decisions, no matter how big or small, cannot be overstated. Decision Making For Dummies is a candid resource that helps leaders understand the impact of their choices, not only on business, but also on their credibility and reputation. Designed for managers, business owners, and anyone else who makes tough decisions on a daily basis, this guide helps you figure out if the decisions you're making are the right ones.